Avaliação do saneamento ambiental em assentamentos de reforma agrária utilizando o Método de Análise Hierárquica de processos - Barros, Elaine Franciely dos Santos (2013)
The absence or disability of environmental sanitation systems causes serious environmental and social problems . Large portion of the population lives in poor sanitation, primarily those living in rural areas . This fact tailpiece directly to agrarian reform , where the absence of public policies directed to this aspect , lack of technical assistance and insufficient funds for the construction of housing, makes many residents adopt techniques and improper practices that harm your health and the environment . The aim of this study was to evaluate the environmental sanitation conditions in agrarian reform settlements using the Analytic Hierarchy Process ( AHP ) . The method was structured for the analysis of environmental sanitation in rural areas , establishing a hierarchical structure considering the aspects related to sanitation and socioeconomic conditions , determining the weights of criteria through analysis of interviews with experts in the field and elaboration of the form data collection . The application form was held in February 2013 in settlements in the region Pinga - Fogo , municipality of Miners , and settlement Don Carmelo , Caiapônia municipality , both in the state of Goiás After application form , which determined the weights of each criterion analyzed in the area , went to the processing and determination of local priorities and global settlement of each and comparing them . The AHP method allowed visited lots of hierarchy according to the conditions of each sub-criterion (water supply , sewerage and solid waste ) and analysis criteria ( sanitation and socioeconomic conditions ) for settlement and then comparing them . Besides having to prioritization of lots , it was possible to diagnose which were the main criteria for interference in local conditions , which allows for better targeting and prioritization of actions aimed at improving sanitation and hence the quality of life of local community . According to the results, the settlements of the region Pinga - Fogo had better conditions in all sub-criteria and criteria examined , compared with the settlement Don Carmelo.